2010
DOI: 10.1073/pnas.1002653107
|View full text |Cite
|
Sign up to set email alerts
|

Role for the nuclear receptor-binding SET domain protein 1 (NSD1) methyltransferase in coordinating lysine 36 methylation at histone 3 with RNA polymerase II function

Abstract: The NSD (nuclear receptor-binding SET domain protein) family encodes methyltransferases that are important in multiple aspects of development and disease. Perturbations in NSD family members can lead to Sotos syndrome and Wolf-Hirschhorn syndrome as well as cancers such as acute myeloid leukemia. Previous studies have implicated NSD1 (KMT3B) in transcription and methylation of histone H3 at lysine 36 (H3-K36), but its molecular mechanism in these processes remains largely unknown. Here we describe an NSD1 regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 45 publications
6
106
0
1
Order By: Relevance
“…S1). PHD5-C5HCH NSD3 showed no or very weak binding to other histone peptides such as H3 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), H3 (16 -35), H3 (26 -45), H4 (1-19), H2A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and H2B (1-19) irrespective of their modification states (Fig. 1C).…”
Section: Phd5-c5hchmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). PHD5-C5HCH NSD3 showed no or very weak binding to other histone peptides such as H3 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), H3 (16 -35), H3 (26 -45), H4 (1-19), H2A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and H2B (1-19) irrespective of their modification states (Fig. 1C).…”
Section: Phd5-c5hchmentioning
confidence: 99%
“…Several reports have revealed that NSD family members are possibly recruited to specific gene loci. NSD1 binds upstream of the bone morphogenetic protein 4 promoter, enforces H3K36 methylation levels within this region, and thus promotes bone morphogenetic protein 4 transcription (19). NSD3, LSD2 (an H3K4-specific demethylase, lysine demethylase 2, also known as KDM1B), and G9a (an H3K9-specific methyltransferase, also known as EHMT2) form complexes in vivo, predominantly localize to the gene bodies of actively transcribed genes and may coordinate modifications at H3K4, H3K9, and H3K36 during elongation for optimal transcription (20).…”
mentioning
confidence: 99%
“…In budding yeast, Set2 is the sole H3K36-specific methyltransferase (9). In higher eukaryotes, several enzymes have been reported to be H3K36-specific methyltransferases (7), including HYPB, which is the primary H3K36-specific trimethylase (10 -12), and NSD1, NSD2, NSD3, and ASH1L, which are best characterized as H3K36-specific dimethylases (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…H3K9 (a.a. 5-11) peptide is stabilized by hydrogen bonds with Phe1997, Thr2001, Arg2018, Met2020, Met1999, Tyr2059, Glu2062, Cys2063, Leu2064 and Asn2066 in NSD1, with Asp1112, Met1118, Thr1120, Arg1137, Met1139, Leu1183 and Asn1185 in NSD2, and with Met1200, Met1221, Asn1267, Asn1197, Phe1198, and Thr1270 in NSD3. H3K27 (a.a. [23][24][25][26][27][28][29] peptide is stabilized by hydrogen bonds with Thr1995, Phe1997, Met1999, Arg2018, Met2020, Asn2021, Cys2063, Asn2066 and Thr2069 in NSD1, with Tyr1091, Asp1112, Thr1114, Phe1116, Thr1120, Arg1137, Met1139, Tyr1178, Asp1181, Leu1183, Asn1185 and Thr1188 in NSD2, and, with Thr1196, Phe1198, Met1200, Arg1219, Met1221, Asp1263, Cys1264, Leu1265, Asn1267, Arg1269 and Thr1270 in NSD3. H3K36 (a.a. 32-38) peptide is stabilized by hydrogen bonds with Asp1193, Phe1997, Met1999, Arg2018, Met2020, Asn2021, Glu2062 and Asn2066 in NSD1, with Thr1114, Phe1116, Arg1137, Met1139, Leu1180, Cys1182, Gly1184, Asn1185 and Glu1186 in NSD2, and, with Thr1270, Thr1196, Phe1198, Met1200, Arg1219, Met1221, Asp1263 and Cys1264 in NSD3.…”
Section: Molecular Binding Details Of H3k4 H3k9 H3k27 H3k36 H3k79mentioning
confidence: 99%
“…The amplification of NSD1 has been reported in multiple myeloma, lung cancer, neuroblastoma and glioblastoma. The amplification of either NSD1 or NSD2 triggers cellular transformation [21][22][23][24][25][26][27][28]. NSD2 is associated with tumor aggressiveness or prognosis in most types of cancers, including prostate cancer and multiple myeloma and is overexpressed in at least 15 different cancers [9,10,17,18,20,21,25,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%